River models physical vs. mathematical. - Castro, Peter P.M.
Rigid bed physical and mathematical modelling are each discussed at review level. A brief historical background, an introduction to the theoretical basis for validity, and some sub-classifications and variants are included. The two techniques are then compared, and some criteria for selection of method to use are mentioned. It is suggested that problem definition should govern in the choice of models. Recent trends that are radically changing the criteria are also mentioned.